Сulture of speech and communication efficiency (Journal of Pedagogical Inventions and Practices, 2023)
The culture of speech and communication are important in the development and formation of a person as a person and today education places great emphasis on this aspect. In the meantime, the education and culture are two interrelated processes, language can introduce education into the context of culture. In the history of mankind, the role of language in the life of society is increasing. The volume of circulating information per capital can be an indicator of the level of development of a society. The purpose of writing this work is to study the features of culture and the conditions for the effectiveness of communication. The main tasks of this work are to analyze the literature on the research topic, to reveal the main concepts and problems of the topic, to summarize the work done.